A CONTRIBUIÇÃO DO COORDENADOR PEDAGÓGICO NO DESENVOLVIMENTO DAS PRÁTICAS PEDAGÓGICAS DOS DOCENTES DA EDUCAÇÃO PROFISSIONAL DE NÍVEL TÉCNICO - Balsamo, Simone (2019)
The research aims to investigate the reflections and the influence of pedagogical coordination on the teaching practice of vocational education at the technical level, aiming at the contributions to the improvement of the learning teaching process. Part of the premise and observation is that most of the teachers at this level of education do not have the necessary pedagogical training, which makes it difficult to understand the didactic-pedagogical techniques, and the day-to-day methodologies applied in the institution and, therefore, their performance offers weaknesses in their performance in the teaching-learning process. Teachers report difficulties in making themselves understood, as well as in breaking the paradigm of content transmitters or reproducers, in view of the contemporary conception desirable by all educational institutions aligned to the new times, which expect teachers to incorporate a practice interactionist, mediating and innovative, who find new ways for their practice, through the intervention of pedagogical coordination, in order to achieve continuous improvement of the teaching and learning process. In order to approach this topic in depth, a qualitative research was developed, according to the methodological conceptions of Gil, Severino, Demetriini, Cruz Neto, Minayo, Franco and Britto-Jr. and Feres-Jr., who supported this work, from the construction of the protocol protocols of research to the analysis of the content of the interviews. The interviewees' reports allowed the dialogue between the researcher and the subjects to approach the subject. As a theoretical basis, the authors were studied: Domingues; Vasconcelos, who discuss the role and the role of the pedagogical coordinator, and in the discussion of the conception of teaching practice, the authors: Cunha; Franco; Marques; Altet, Paquay e Perrenoud and Tardif. In the research, 14 interviews with the teachers of the technical courses and pedagogical coordinators were carried out to know their experience in school environments, in order to perceive their needs and difficulties in their daily school life, as far as pedagogical practice is concerned. Finally, this study made it possible to understand the need for the contribution of pedagogical coordination in the pedagogical practices of professional education teachers of technical level.